The Utilization of Postnatal Care in South Sulawesi (Data Analysis of the Indonesia Demographic and Health Survey 2017) - Akmal; Apik Indarty Moedjiono; Muhammad Rachmat (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
The main problem that is still faced with maternal health in Indonesia isthe high Maternal Mortality Rate (MMR). It is estimated that 60% ofmaternal deaths in Indonesia occur after postpartum, and nearly 50% ofdeaths during childbirth occur within the first 24 hours after delivery.Some causes of maternal death, such as postpartum complications andpostpartum bleeding, can be prevented through the puerperal careprogram. The study aims to determine the factors associated with apostpartum examination in South Sulawesi Province. This study usescross-sectional study design in 393 couple’s age 15-49 years by usingdata from IDHS 2017. The hypothesis was tested with a chi-square test(p<0.05). The results obtained by variables related to the utilization ofchildbirth services in South Sulawesi are education (p=0.000), birth order(p=0.026), place of childbirth (p=0.000), wealth quintiles (p=0.000),distance to health facilities (p=0.020), and complication during delivery(p=0.000). Variables not related to postpartum service use are age(p=0.507), occupation (p=0.232), and ANC visit (p=0.077). A compre-hensive effort is needed by involving various media and elements ofsociety to encourage mothers to use health care, especially after post-partum.